2008
DOI: 10.1103/physrevb.78.094420
|View full text |Cite
|
Sign up to set email alerts
|

Jahn-Teller inactivity and magnetic frustration inGeCo2O4probed by ultrasound velocity measurements

Abstract: Ultrasound velocity measurements of cubic spinel GeCo 2 O 4 in single crystal were performed for the investigation of shear and compression moduli. The shear moduli in the paramagnetic state reveal the absence of Jahn-Teller activity despite the presence of orbital degeneracy in the Co 2+ ions. Such a Jahn-Teller inactivity indicates that the intersite orbital-orbital interaction is much stronger than the Jahn-Teller coupling. The compression moduli in the paramagnetic state near the Néel temperature T N revea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
1
24
1
Order By: Relevance
“…Since the magnetic structure in GeCo 2 O 4 is the same as that in GeNi 2 O 4 below T N2 , it is likely that J 4 , J 0 3 , and J 3 also play important roles in GeCo 2 O 4 . Although the Curie-Weiss temperature in GeCo 2 O 4 was estimated to be 81 K, 14) 57 K, 15) and 41 K, 16) Lashley et al claimed that these large Curie-Weiss temperatures were estimated incorrectly. 11) They analyzed the magnetic susceptibility including the excited crystal-field levels and found that the free ion model describes the observed values reasonably well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the magnetic structure in GeCo 2 O 4 is the same as that in GeNi 2 O 4 below T N2 , it is likely that J 4 , J 0 3 , and J 3 also play important roles in GeCo 2 O 4 . Although the Curie-Weiss temperature in GeCo 2 O 4 was estimated to be 81 K, 14) 57 K, 15) and 41 K, 16) Lashley et al claimed that these large Curie-Weiss temperatures were estimated incorrectly. 11) They analyzed the magnetic susceptibility including the excited crystal-field levels and found that the free ion model describes the observed values reasonably well.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al suggested that the orbital frustration disturbs the orbital ordering in the cubic phase and the structural transition quenches the orbital degeneracy. 16) The magnetic structure below T N is affected by the t 2g orbitals, which contribute to the direct Co-Co coupling. Since the kagomé and triangular spins order simultaneously, it is expected that the coupling between kagomé and triangular planes is stronger in GeCo 2 O 4 than in GeNi 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The sound velocity or the elastic modulus is a useful probe which can extract symmetry-resolved thermodynamic information in the frustrated magnets 17,18 . In MnV 2 O 4 , recent ultrasound velocity measurements observed a huge elastic softening on cooling in the cubic paramagnetic (PM) phase, which is considered to be driven by the coupling of lattice to orbital-spin-coupled fluctuations 19 .…”
mentioning
confidence: 99%
“…The sound velocity or the elastic modulus is a useful probe enabling symmetry-resolved thermodynamic information to be extracted from frustrated magnets. 16,17,[24][25][26][27][28][29][30][31][32] As mentioned earlier, the observed elastic anomalies in the chromite spinels ACr 2 O 4 inferred the coexistence of spin-JT fluctuations and molecularspin excitations in the PM phase. 16,17 The present study finds elastic anomalies in ZnFe 2 O 4 that suggest the evolution of a dynamical molecular-spin state at low temperatures without undergoing precursor spin-lattice fluctuations and spin-lattice ordering, which is a behavior uniquely different from another spin-frustrated molecular-spin system ACr 2 O 4 .…”
mentioning
confidence: 70%